STUDY ON FASHION DESIGN STUDENTS' DIFFICULTIES IN THE 2018 EXHIBITION AND FASHION DESIGN AND DEMONSTRATION COURSES AT THE STATE UNIVERSITY OF MALANG - Nurul Aini; Endang Prahastuti; Nur Ziyan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2022)
Fashion has become a part of modern society. Fashion designers show today's fashion works through activities such as exhibitions. The Bachelor of Fashion Education and Diploma of Fashion Design, Faculty of Industrial Technology, State University of Malang, hosted a show as a part of the Exhibition and Fashion Design and Demonstration courses. Students who participated reported problems at certain stages of the exhibition process. This study aimed to analyze these difficulties using a quantitative approach descriptively. Questionnaires were used for the data collection process with 58 samples. The results suggested that the main problem lay in production design and inspiration. Students' design challenges were material choices, storyboard creation, design principles application, and ideas generation. During the fashion production phase, a difficulty occurred during the sewing process and creating an action plan. The main organizational problem for students was cooperation with internal committees at the organizational stage. Keywords: exhibition, difficulty, fashion creation, demonstration